STUDI KASUS: PENGARUH ACCEPTANCE AND COMMITMENT THERAPY TERHADAP SELF-COMPASSION INDIVIDU DENGAN ORANGTUA BERCERAI - Wella Ayu Cahaya; Hartanti Hartanti; Nurlita Endah Karunia (Perpustakaan Universitas Surabaya, 2018)
The aim of this study is to see the impact of Acceptance and Commitment Therapy (ACT) on self-compassion of individual with divorced parents. The research approach uses mixed methods with concurrent triangulation strategy. Quantitative research used a single case experimental method involving single subject who is a female at the age of emerging adulthood, having divorced parents since subject on adolescent age, and having low self-compassion. ACT intervention were given 6 sessions over 2 weeks. The results show that ACT improves subject’s self-compassion. Common humanity and mindfulness increase after intervention and self-kindness increases in 2 weeks after intervention. There’s also a decrease in all negative aspects of self-compassion. ACT raises subject’s awareness to do self-compassion and increase ability to overcome negative thoughts and emotions through the techniques taught. On the other hand, qualitative result show that ACT hasn’t been able to completely eliminate negative thoughts and emotions. The influencing factor is the nature of the ACT that doesn’t aim to eliminate negative thoughts and emotions instead exercises the ability to overcome them. Family support and personality also affect the process and outcome of the intervention.